2023
DOI: 10.1128/spectrum.03591-22
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Flexible RT-qPCR Surveillance Platforms To Detect SARS-CoV-2 Mutations

Abstract: Denmark weathered the SARS-CoV-2 crisis with relatively low rates of infection and death. Intensive testing strategies with the aim of detecting SARS-CoV-2 in symptomatic and nonsymptomatic individuals were available by establishing a national test system called TestCenter Denmark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In our study, we made a head-to-head comparison of the RT-PCR variants assays with WGS. Previous studies [ 15 ; 19 ] have also explored the use of variant detection by RT-PCR from nasopharyngeal and from waste-water, with high levels of concordance. However, our study provides new information and insights of special importance for patient management: this is the first study to use variant assays for both SARS-CoV-2 diagnosis and variant identification, vital for treatment decisions, especially in severe cases where certain Omicron variants may resist monoclonal antibodies [ 12 ; 20 ]; we also, showed excellent assay specificity and positive predictive values, pivotal for clinical decisions; finally, our data support these assays to bolster regional and national variant surveillance, particularly beneficial for low- and middle-income countries with limited access to whole genome sequencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we made a head-to-head comparison of the RT-PCR variants assays with WGS. Previous studies [ 15 ; 19 ] have also explored the use of variant detection by RT-PCR from nasopharyngeal and from waste-water, with high levels of concordance. However, our study provides new information and insights of special importance for patient management: this is the first study to use variant assays for both SARS-CoV-2 diagnosis and variant identification, vital for treatment decisions, especially in severe cases where certain Omicron variants may resist monoclonal antibodies [ 12 ; 20 ]; we also, showed excellent assay specificity and positive predictive values, pivotal for clinical decisions; finally, our data support these assays to bolster regional and national variant surveillance, particularly beneficial for low- and middle-income countries with limited access to whole genome sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR allows to obtain and report the results on the same day, and may be easily implemented in the routine of a clinical microbiology laboratory [ 14 ; 15 ]. In this paper, we aimed to demonstrate the ability of RT-PCR to detect SARS-CoV-2 and its variants in a single test, increasing the number of samples that can be analysed.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical samples were sequenced with targeted NGS and screened with these RT-PCR assays and showed a ~99.5% concordance. Another study designed two flexible, multiplexed RT-qPCR platforms for small- and large-scale screening, using MGB probes, to detect the L452R, E484K, N501Y and ΔH69/V70 deletion in clinical samples from Denmark ( Spiess et al., 2023 ). Relative to our study, a similar approach was taken where the multiplexed assays comprised two probes – one to detect the wild-type nucleotide sequence and one to detect the mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this limitation, we showed that all probes were specific for their cognate sequences and to independently confirm the SNP calling, regions harbouring respective mutation in the S -gene were amplified and Sanger sequenced. Other studies have used either Sanger sequencing or WGS for confirmation ( Erster et al., 2021 ; Aralis et al., 2022 ; Moisan et al., 2023 ; Spiess et al., 2023 ; Zare Ashrafi et al., 2023 ). A large proportion of samples, particularly from Clinical Site 2, could not be confirmed as PCR failed to generate amplicons for sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not quite clear whether the Omicron sub-variants differ from each other in the severity of the clinical outcome, local diagnostic laboratories still need to constantly monitor their epidemiology. Due to their continuous evolution and extensive simultaneous spread worldwide, there are very limited molecular detection tests available that are also capable of distinguishing specific Omicron sub-variants [ 27 , 28 , 29 , 30 ]. In some cases, the escape from molecular detection, by S dropout (the so-called “S gene target failure” or SGTF) has been related to the detection of BA.4 and BA.5 sub-lineages.…”
Section: Discussionmentioning
confidence: 99%